e-Infrastructure and e-Services for Developing Countries : 6th International Conference, AFRICOMM 2014, Kampala, Uganda, November 24-25, 2014, Revised Selected Papers - Nungu, Amos.; Pehrson, Bjorn; Sansa-Otim, Julianne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 6th International Conference on e-Infrastructure and e-Services for Developing Countries, AFRICOMM 2014, held in Kampala, Uganda, November 24-25, 2014. The 31 revised full papers were carefully selected from 57 submissions and cover topics such as communication infrastructure, health, IoT, cloud computing and TVWS, ICT4D applications, access to information, and ICT4D miscellaneous.
Throughput Performance of Interference Mitigation Techniques in Cognitive Femtocell Networks -- Inclusive Ubiquitous Access - A Status Report -- Performance Evaluation of Scheduling Algorithms for Fixed WiMAX Network -- Enhancing Performance in Cognitive Radio Networks -- Enabling converged satellite and terrestrial access networks -- Empirical Path Loss Models for 802.11n Wireless networks at 2.4Ghz in rural regions -- Quantifying the Effects of Circuitous Routes on the Latency of Intra-Africa Internet Traffic: A Study of Research and Education Networks -- Towards centralized spectrum allocation optimization for multi-channel wireless backhauls -- Towards a Practical Cognitive Channel Allocation Scheme.
Keywords: Computer science; Computer Communication Networks; Computers and Society; Computer Communication Networks; Information Systems Applications (incl. Internet).; Computer Applications